P1 Psychometric properties of health-related quality of life tools for idiopathic pulmonary fibrosis. (12th November 2019) - Kim, J; Clark, A; Birring, S; Atkins, C; Whyte, M; Wilson, AM
Abstract : Background: Assessing health-related quality of life (HRQOL) in idiopathic pulmonary fibrosis (IPF) is important clinically and for research. As there is no universally agreed HRQOL tool for IPF, a variety of different tools have been used. We aimed to compare the psychometric properties of various HRQOL tools used IPF, assess their relationship with 1-year mortality and determine minimal important clinical difference (MCID). Methods: This was an observational prospective longitudinal multicentre study, involving 238 people with IPF. Participants were asked to complete HRQOL tools including EuroQol 5 dimension (EQ-5D-5L), King's brief interstitial lung disease questionnaire (K-BILD) and St George's Respiratory questionnaire (SGRQ), at approximate three-monthly intervals over a 12 month period. Physiological measurements including spirometry and 6 minute walking distance were captured and matched with questionnaires. Results: There were 778 patient assessments with each individual having an average of 3.3 sets of questionnaires. All questionnaires showed good internal consistency with Cronbach's alpha coefficients of >0.8. There were strong correlations between questionnaires but not with physiological measurements. People with FVC% predicted ≤70% had higher mean SGRQ and MRC scores, and lower mean EQ5D and K-BILD score. People in upper tercile of baseline KBILD and EQ-5D-5L (better health status) had significantly reduced risk of deaths than those in the lower tercile (HR 0.06; 95% CI 0.01–0.42 and HR 0.27; 95CI 0.09–0.81, respectively). Those in the upper tercile of SGRQ (worse health status) had more than 3-fold increased risk of mortality than those in the lower tercile (HR 4.65; 95% CI 1.32–16.62). The MCID (anchor method) for K-BILD was 2.3 and SGRQ was 3.9. Conclusion: We recommend using the MRC dyspnoea scale rather than UCSD SOBQ, given it brevity and better known groups validity. Both the K-BILD and SGRQ were appropriate disease specific HRQOL tools for assessing people with IPF but we recommend the use of K-BILD, given its brevity and stronger relationship to mortality.